The Ideal Strengthening of the Attorney General's Authority in Civil and Administrative Law to Provide Legal Assistance in the Implementation of Strategic Projects - Sukandi Maku; Erman I. Rahim; Suwitno Y. Imran (Dinasti Research, 2025)
The objective of this paper is to formulate the ideal strengthening of the Attorney General's Office's authority in the fields of civil and administrative law to provide legal assistance in the implementation of strategic projects. This study employs a normative legal research method using several approaches, namely the Statutory Approach, the Conceptual Approach, and the Case Approach. The research utilizes a data analysis technique based on deductive logic with a prescriptive nature. The findings of this paper indicate that the authority of the Attorney General's Office in the fields of civil and administrative law needs to be strengthened in terms of both substance and structure to support legal assistance for national strategic projects. Pursuant to Article 18 of Law No. 11 of 2021, the Attorney General's Office acts as the State Attorney in both litigation and non-litigation matters in the interests of the state and government. This assistance is carried out through the safeguarding of strategic projects and legal risk mitigation. A paradigm shift from a repressive to a preventive approach is crucial to minimize deviations and support sustainable governance. Therefore, coordination among units, supervision, and comprehensive regulations are necessary to ensure transparency and accountability.